Cover Image, Volume 117, Issue 12. Issue 12 (5th June 2017) - Unknown
Abstract : Conceptually, density functional theory (DFT) depends totally on electron density. However, the kinetic energy density functional (KEDF) form is not known exactly and its available approximations are not accurate enough. On article e25373 (DOI:10.1002/qua.25373 ), Alharbi and Kais present a newpromising approach, based on determining axiomatically the physically acceptable forms of D‐dimentional KEDF and then statistically fitting those using exactly solvable potentials. The method can open a new search for highly accurate KEDF and can be an important step toward finding a universal energy functional ‐ a critical outstanding problem in DFT. (DOI:10.1002/qua.25373 ).